Implementasi Kebijakan Perlindungan Anak Terhadap Kekerasan Anak di Kota Bandung Tahun 2023 - Rhaisa Indriani; Nandang Alamsyah Delianoor; Novie Indrawati Sagita (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2025)
This research analyses the implementation of child protection policies against child abuse in Bandung City in 2023 using qualitative methods and a narrative approach. Data was obtained through in-depth interviews with officials of the Office of Women's Empowerment and Child Protection (DP3A) and the Regional Technical Implementation Unit for Women and Children Protection (UPTD PPA), supported by a literature study. The results showed that the Community-Based Integrated Child Protection (PATBM) program, Senandung Perdana application, and intensive socialization had implemented child protection policies. However, policy implementation faces significant obstacles, such as limited human resources, only 16 counselors and advocates, and inadequate budget allocations. The high number of reported cases of child abuse not only shows the complexity of the problem but also reflects the success of socialization. This research emphasizes the need for continuous evaluation, increased resources, and cross-sector collaboration to ensure child protection policies' overall and sustainable effectiveness in Bandung City.